The Actual Problems of Modern Spain - N. E. Anikeeva (Vestnik MGIMO-Universiteta)
The important aim of national and Spanish historiography and political science is to study history and foreign policy of modern Spain. The author studied articles and monographies of spanish politicians and researchers ( M. Rahoy, I. Aries, A. Rubalcaba, I. Molina) for the preparation of this article during the scientific trip to Madrid (Complutense University, Faculty of Political Science and Sociology), which was held in the framework of cooperation between the Bank Santander and MGIMO (University). The paper analyzes the political and economic aspects of life in Spain, and its foreign policy of the period of government of Mariano Rajoy (from 2011 to the present time). The article is dedicated to actual problems of modern Spain: the economy and the priorities of the government of M.Rajoy, the problem of separatism and political system of the country. Modern Spain is still recovering economically from the euro debt crisis and continues to struggle with near-record unemployment. Domestic economic recovery of Spain and the country's foreign position are closely linked. The European integration process still remains the main strategic task of the spanish foreign policy. Spain increases its role in world politics and obtains a non-permanent UN's Security Council seat for the 2015-2016 term.